Compartmentalized protective and detrimental effects of endogenous MIF mediated by CXCR2 in a mouse model of myocardial ischemia/reperfusion - Liehn, Elisa A. (Arterioscler Thromb Vasc Biol, 2013)
OBJECTIVES: Here we aimed to clarify the role of CXCR2 in the macrophage migration inhibitory factor (MIF)-mediated effects after myocardial ischemia and reperfusion (I/R). As a pleiotropic chemokine-like cytokine, MIF has been identified to activate multiple receptors including CD74 and CXCR2. In models of myocardial infarction (MI), MIF exerts both pro-inflammatory effects and protective effects in cardiomyocytes. Likewise, CXCR2 displays opposing effects in resident versus circulating cells. APPROACH AND RESULTS: Using bone marrow (BM) transplantation, we generated chimeric mice with CXCR2(−/−) BM-derived inflammatory cells and wild-type resident cells (wt/CXCR2(−/−)), with CXCR2(−/−) cardiomyocytes and wild-type BM-derived cells (CXCR2(−/−)/wt) and wild-type controls reconstituted with wild-type BM (wt/wt). All groups were treated with anti-MIF or isotype control antibody before they underwent myocardial I/R. Blocking MIF increased infarction size and impaired cardiac function in wt/wt and wt/CXCR2(−/−) mice but ameliorated functional parameters in CXCR2(−/−)/wt mice, as analyzed by echocardiography and Langendorff perfusion. Neutrophil infiltration and angiogenesis were unaltered by MIF blockade or CXCR2 deficiency. Monocyte infiltration was blunted in wt/CXCR2(−/−) mice and reduced by MIF blockade in wt/wt and CXCR2(−/−)/wt mice. Moreover, MIF blockade attenuated collagen content in all groups in a CXCR2-independent manner. CONCLUSIONS: The compartmentalized and opposing effects of MIF after myocardial I/R are largely mediated by CXCR2. Whereas MIF confers protective effects improving myocardial healing and function through CXCR2 in resident cells, complementing paracrine effects through CD74/AMPK, it exerts detrimental effects on CXCR2-bearing inflammatory cells, increasing monocyte infiltration and impairing heart function. These dichotomous findings should be considered, when developing novel therapeutic strategies to treat MI.